Sets or frequencies? How to help people solve conditional probability problems - Moro, Rodrigo (2011)
Since the 1970s, the Heuristics and Biases Program in Cognitive Psychology has shown that people do not reason correctly about conditional probability problems. In the 1990s, however, evolutionary psychologists discovered that if the same problems are presented in a different way, people's performance greatly improves. Two explanations have been offered to account for this facilitation effect: the natural frequency hypothesis and the nested-set hypothesis. The empirical evidence on this debate is mixed. We review the literature pointing out some methodological issues that we take into account in our own present experiments. We interpret our results as suggesting that when the mentioned methodological problems are tackled, the evidence seems to favour the natural frequency hypothesis and to go against the nested-set hypothesis. © 2011 Psychology Press Ltd.